Influence of Cultivars and Seed Thermal Treatment on the Development of Fungal Pathogens in Carrot and Onion Plants - Martin Koudela (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
Carrot and onion are vegetables representing an important segment of fresh market. They suffer from serious fungal diseases that can inflict great damage on crops, i.e. alternaria leaf blight, peronospora downy mildew, and botrytis neck rot. The resistance of selected carrot and onion cultivars important for the production of vegetables in the Czech Republic was tested by exposure to targeted infection by the above fungal pathogens. The exposure of eleven carrot cultivars to spores of Alternaria dauci showed that the most resistant and sensitive cultivars were Katrin, Cortina F1, Afalon F1 and Favorit, Tinga, Berlika F1, respectively. A targeted infection of onion cultivars with Botrytis aclada clustered them into three groups: Amfora F1, Bolero, Tosca, Triumf F1 (strong resistance), Avalon, Grenada (medium resistance), Alice, Karmen, Všetana (low resistance). Similar groups were distinguished also after the infection with Peronospora destructor: Avalon, Bolero, Tosca (strong resistance), Alice, Amfora F1, Grenada, Karmen, Triumf F1 (medium resistance),Všetana (low resistance). Hot water treatment of carrot seeds applied after the inoculation with A. dauci decreased the development of the infection 1.3-2.3-fold, whereas the protective effect observed with onion seeds against the infection by P. destructor and B. aclada was lower.